A stroke recovery trial development framework: Consensus-based core recommendations from the Second Stroke Recovery and Rehabilitation Roundtable. Issue 8 (October 2019) - Bernhardt, Julie; Hayward, Kathryn S; Dancause, Numa; Lannin, Natasha A; Ward, Nick S; Nudo, Randolph J; Farrin, Amanda; Churilov, Leonid; Boyd, Lara A; Jones, Theresa A; Carmichael, S Thomas; Corbett, Dale; et al.
A major goal of the Stroke Recovery and Rehabilitation Roundtable (SRRR) is to accelerate development of effective treatments to enhance stroke recovery beyond that expected to occur spontaneously or with current approaches. In this paper, we describe key issues for the next generation of stroke recovery treatment trials and present the Stroke Recovery and Rehabilitation Roundtable Trials Development Framework (SRRR-TDF). An exemplar (an upper limb recovery trial) is presented to demonstrate the utility of this framework to guide the GO, NO-GO decision-making process in trial development.